Glia-Neurons Cross-Talk Regulated Through Autophagy - Damulewicz, Milena; Szypulski, Kornel; Pyza, Elzbieta (Frontiers in Physiology, 2022)
Autophagy is a self-degradative process which plays a role in removing misfolded or aggregated proteins, clearing damaged organelles, but also in changes of cell membrane size and shape. The aim of this phenomenon is to deliver cytoplasmic cargo to lysosome through the intermediary of a double membrane-bound vesicle (autophagosome), that fuses with lysosome to form autolysosome, where cargo is degraded by proteases. Products of degradation are transported back to the cytoplasm, where they can be re-used. In the present study we showed that autophagy is important for proper functioning of the glia and that it is involved in the regulation of circadian structural changes in processes of the pacemaker neurons. This effect is mainly observed in astrocytes-like glia, which play a role of peripheral circadian oscillators in the Drosophila brain.